Novel insights into MSC-EVs therapy for immune diseases - Peilong Lai; Jianyu Weng; Liyan Guo; Xiaomei Chen; Xin Du (BMC, 2019)
Abstract Mesenchymal stromal cells (MSC) are a heterogeneous cell population with self-renewal and the ability to differentiate into different lineages. The novel regulatory role of MSC in both adaptive and innate immune responses got extensive investigation and MSC have been widely used in clinical trials as immunosuppressive agents for autoimmune and inflammatory diseases, including graft-versus-host disease (GVHD), multiple sclerosis (MS), systemic lupus erythematosus (SLE), chronic kidney disease, etc. Recent studies have found that MSC exerted their immunomodulation function through secreting extracellular vesicles (EVs), which delivered parent cell cargo to recipient cells without oncogenicity or variability. Since MSC-EVs exhibit most of the properties of MSC and take advantage of their cellular immunomodulatory fuction, MSC-EVs appear to a promising none-cell therapy in various human diseases. In this review, we summarize the pivotal roles of MSC-EVs as agents for immunotherapy in diseases.